Youth, urban space and the Right to the City: Contributions to social education (Foro de Educacion, 2019)
The urban space is configured through a complex interactive, collective and dynamic development. Young people, like the rest, should be able to participate in its production from their uniqueness. However, the urban reality shows that these processes tend to promote the exclusion of those subjects who do not conform to a finalist and unconflicted conception of that space. Through symbolic and material barriers, certain urban areas are encapsulated, conditioning and, sometimes, blocking the vital trajectories of those who inhabit them. The present article, synthesis of a more extensive work, takes the form of theoretical reflection and builds its arguments from the hand of several references from both urban anthropology and critical urbanism, as well as social education and social pedagogy. Its structure is developed in relation to three objectives. The first is to share some guidelines on contemporary urbanization processes that result in the exclusion and urban expulsion of many young people. The second is to recognize how these processes and urban productions impact on these people. And finally, the third is committed to introducing elements of reflection that facilitate the development of socio-educational strategies that promote the appropriation of the urban space from the recognition of the Right to the City of youth.